2006
DOI: 10.1002/cphc.200600402
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Amplification of Porphyrin Assemblies Exclusively Constructed from Achiral Porphyrin Derivatives

Abstract: Two achiral porphyrin derivatives, 5,10,15,20-tetrakis(4-methoxyphenyl)-21H,23H-porphine (TPPOMe) and 5,10,15,20-tetrakis(4-hydroxyphenyl)-21H,23H-porphine (TPPOH), were spread onto an air/water interface. The spreading films were transferred onto solid substrates by the Langmuir-Schaefer (LS) method. Although both of the porphyrin derivatives are achiral species, the transferred LS multilayer films shows macroscopic supramolecular chirality, which is suggested to be due to the spontaneous symmetry breaking th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 93 publications
1
33
0
Order By: Relevance
“…If the sample intrinsically had genuine chirality, both the methods would give the same results. [10,11] We measured the CD spectra of the LS film of H 2 OEP deposited from the hydrochloric acid subphase according to the above-described methods as an example to illustrate the authenticity of the observed macroscopic chirality. As shown in Figure 3A, the angle dependence of the CD amplitude was determined by the difference between the maximum value at 351 nm and minimum value at 411 nm, and the corresponding angle dependence of the background was determined by the difference between the values at the lower edge at 250 nm and upper wavelength edge at 600 nm, which are displayed as filled squares and circles, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…If the sample intrinsically had genuine chirality, both the methods would give the same results. [10,11] We measured the CD spectra of the LS film of H 2 OEP deposited from the hydrochloric acid subphase according to the above-described methods as an example to illustrate the authenticity of the observed macroscopic chirality. As shown in Figure 3A, the angle dependence of the CD amplitude was determined by the difference between the maximum value at 351 nm and minimum value at 411 nm, and the corresponding angle dependence of the background was determined by the difference between the values at the lower edge at 250 nm and upper wavelength edge at 600 nm, which are displayed as filled squares and circles, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11]19] Authenticity of the observed macroscopic chirality: It has been suggested that the authenticity of the observed chirality through conventional CD measurement could not be exclusively determined for solid-state samples, because the detected CD spectra are often accompanied by artifacts which usually originate from the interaction between the macroscopic anisotropies of a sample such as birefringence and linear dichroism (LD). [20] Effective strategies for the CD measurement of thin solid films have been proposed by Spitz and co-workers, [21] and used by us previously, [10,11] to validate the authenticity of the chirality detected from the LB or LS films. This can be achieved in two ways.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there has been growing interest in the supramolecular assembly of achiral molecules into chiral nanostructures with a controlled helical sense [1][2][3][4] . Among them, chiral J-aggregates of achiral cyanine dyes [5][6][7][8] and porphyrins [9][10][11][12] are particularly interesting because of their potential applications to optoelectronic materials and photosynthesis, as well as the possible explanation for the origin of biomolecular homochirality [13,14] .…”
Section: Introductionmentioning
confidence: 99%